A4.12 Hand bone loss in early rheumatoid arthritis but not in psoriatic arthritis after 1 year of treatment as measured by digital x-ray radiogrammetry. (13th February 2015) - Szentpetery, A; Haroon, M; Gallagher, P; Heffernan, E; FitzGerald, O
Abstract : Background and objectives: Despite RA and PsA share similar pathophysiological concepts, there are profound differences in the anatomical localisation of inflammatory lesions and in periarticular bone structure. Digital X-ray radiogrammetry (DXR) is a sensitive method for quantifying changes in periarticular bone mineral density (DXR-BMD) in the early phase of the disease. The aim of this study was to compare changes in hand BMD as measured by DXR in early, treatment-naïve RA to PsA patients prior to and 3, 12 months after introducing an anti-rheumatic drug. Methods: Recent-onset (<12 months), active, treatment naïve PsA and RA patients were selected. Hand BMD was measured by DXR based on digitised hand radiographs (Sectra, Sweden) at baseline, 3 and 12 months. Mean DXR-BMD (mg/cm 2 ) values of both hands and changes in DXR-BMD (mg/cm 2 /month) were compared between the two groups. Changes in hand BMD were further analysed by dividing PsA and RA into 3 subgroups based on cut-offs for the categories normal, elevated BMD loss (>-0.25 mg/cm 2 /month) and highly elevated BMD loss (>-2.5 mg/cm 2 /month). Results: 64 patients (32 RA, 32 PsA) were included with median age 43 years. 95% of the patients were started on a DMARD at baseline and stayed on it at 12 months; 12.5% and 34.5% received TNFi in combination with a DMARD, respectively. 69% of RA and 68% of PsA patients were EULAR responders at 3 months, and 80% and 82% at 12 months, respectively. Mean hand DXR-BMD was lower in both diseases at 3 months compared to baseline. In RA DXR-BMD decreased further and was lower at 1 year compared to baseline (p = 0.004) and to 3 months (p = 0.002). In contrast mean DXR-BMD increased from 3 to 12 months in PsA (p = 0.07). Hand BMD was higher in PsA than in RA throughout the study. Patients started on a TNFi in combination with a DMARD had higher hand DXR-BMD at 3 and 12 months comparing with those who started on a DMARD monotherapy (p = 0.015 and p = 0.021, respectively). Among all patients with elevated BMD loss, change in DXR-BMD was less marked in the PsA group compared to RA from baseline to 3 (p = 0.018) and from 3 to 12 months (p = 0.011). Highly elevated bone loss was present only in the RA cohort at 1 year. Conclusions: To our knowledge, this is the first prospective study comparing hand BMD changes in RA to PsA using DXR. Despite intervention of appropriate anti-rheumatic drug and improvement in disease activity measures, we found hand bone loss in RA, but bone gain in PsA after 12 months. Our observations support the hypothesis of different pathomechanisms being involved in hand bone remodelling in PsA.